A comparison of personality traits, learning style, and perceived stress among surgical and nonsurgical residents in a tertiary care hospital in India - Rahul Bansal; Kathleen Anne Mathew; Arya Jith; Dinesh Narayanan (Industrial Psychiatry Journal, 2021)
Introduction: It is often perceived that the presence of a distinct surgical personality plays an important role in predicting success in their surgical career. This study compares the personality profiles, perceived stress, and learning styles of surgical and nonsurgical residents. Aim: The aim of this study is to examine the differences in personality traits, learning style preferences, and perceived stress among surgical and nonsurgical residents. Setting and Design: A cross-sectional study was conducted comparing surgical and non-surgical residents in a tertiary care teaching hospital. Materials and Methods: The 50-item International Personality Item Pool Big- Five Factor Marker questionnaire was used to score 5 personality domains. The 24-item Learning Style Inventory Questionnaire was used to determine the preferential learning styles (visual, auditory, or tactile). The Perceived Stress Scale was administered to assess the perception of stress in the residents. Statistical Analysis: t-test and chi-square test were done for statistical analysis. Results: A statistically significant difference was found in learning style preferences with visual (14.78 ± 3.73 vs. 7.4 ± 2.25) and kinesthetic styles being (13.84 ± 4.37 vs. 6.96 ± 1.47) preferred by surgical residents whereas auditory style was preferred by nonsurgical residents (P < 0.05). Surgical residents scored higher in extraversion (P = 0.00), conscientiousness (P = 0.00), and openness to experience (P = 0.00) which was statistically significant. Nonsurgical residents were found to have a higher perception of stress which was statistically significant (13.40 ± 7.10 vs. 21.12 ± 7.52) (P = 0.01). Conclusion: The significant trait variance supports the concept of surgical personality.